Challenges for the New Century Trends That Will Influence Kentucky's Future - Smith-Mello, Michal; Childress, Michael T.; Watts, Amy L.; Watkins, John F.; Kentucky Long-Term Policy Research Center, Frankfort ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
Trends that will influence Kentucky's future were examined along with policy options for responding to those trends. According to the analysis, the effects of the new economy on Kentucky has been mixed. Although many Kentuckians have benefited from the new economy, the state's least educated and poorest residents are falling further behind the rest of the nation. The inequalities in the areas of income and access to information technology are especially significant. Kentucky has recognized that education is the key to closing these gaps. Access to health care and Kentucky's increasing elderly population are additional areas of concern. Kentucky policymakers will need to devote special attention to the following areas: (1) reducing income inequalities; (2) closing the digital divide; (3) plugging health care gaps; (4) investing in people, especially by increasing investments in early childhood, K-12, postsecondary, and adult education; (5) building social capital; and (6) managing demographic change. (Fifty-three tables/figures are included. Discussions of the following items are appended: income inequality; computer and network usage; selected variables examined in a 2000 survey of 3,000 Kentucky high school students; factors affecting the probability of school attendance; and background information and sample characteristics from a survey completed by 962 Kentuckians aged 45 and older.) (MN)
Availability: Kentucky Long-Term Policy Research Center, 111 St. James Court, Frankfort, KY 40601-8486. Web site: http://www.kltprc.net.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Computers; Access to Education; Adult Education; Aging (Individuals); Change Strategies; Computers; Early Childhood Education; Economic Climate; Economic Development; Education Work Relationship; Educational Finance; Educational Needs; Educational Policy; Educational Trends; Elementary Secondary Education; Employment Patterns; Equal Education; Futures (of Society); Higher Education; Human Capital; Information Technology; Labor Force; Labor Force Development; Middle Aged Adults; Needs Assessment; Older Adults; Outcomes of Education; Policy Formation; Population Trends; Public Policy; Salary Wage Differentials; School Holding Power; Social Capital; State Surveys; Statewide Planning; Strategic Planning; Student Attitudes; Student Characteristics; Trend Analysis; Kentucky; Impact Studies -- Return on Investment; Information Analyses